The Influence of the Presentation of Camera Surveillance on Cheating and Pro-Social Behavior - Jansen, Anja M.; Giebels, Ellen; van Rompay, Thomas J. L.; Junger, Marianne (Frontiers in Psychology, 2018)
Introduction - This paper is aimed at gaining more insight into the effects of camera-surveillance on behavior. This study investigates the effects of three different ways of ‘framing’ camera presence on cheating behavior and pro-social behavior. First, we explore the effect of presenting the camera as the medium through which an intimidating authority watches the participant. Second, we test the effect of presenting the camera as being a neutral, non-intimidating viewer. Third, we investigate whether a participant watching themselves via a camera has an effect on their behavior. In contrast to most studies of camera surveillance, we will conduct our experiments in an indoor setting, enabling us to investigate behavior to a much greater detail. We will also explore possible moderating effects of personality traits. Methods - 86 students participated in this experiment, distributed over four conditions: three different ways of framing the camera presence, plus a control condition. Our main dependent variables were various kinds of cheating and pro-social behavior. We established the participant’s relevant personality traits in a separate session. Results - For cheating behavior, findings showed that the ‘authorative’ way of framing camera presence and the situation in which participants viewed themselves, differed significantly from a situation without camera-surveillance. We did not find significant effects of camera surveillance on pro-social behavior during the experiment. Looking at personality traits, we found an indication that people with an internal locus of control are more inclined to cheat when there is no camera present compared to people with an external locus of control. However, the effects of our manipulations were stronger. Conclusion - These results support the idea that the framing of a camera’s presence does indeed influence cheating behavior, adding to the preventive effects of camera-surveillance. Additionally, this study provides some valuable insights into the influence of camera presence on behavior in general.